2018
DOI: 10.4314/jab.v126i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Distribution spatio-temporelle de la pression du braconnage sur <i>Eidolon helvum</i> (Kerr, 1792), espèce proche de la menace (Côte d’Ivoire, Afrique de l’Ouest)

Abstract: Objectifs : Cette étude vise à étudier la répartition dans l'espace et dans le temps de l'activité de braconnage sur les chauves-souris paillées (qui rendent d'importants services écosystémiques), Eidolon helvum (Kerr, 1792), espèce proche de la menace, de la commune du Plateau (Abidjan, Côte d'Ivoire) afin de dégager des implications pour sa conservation. Méthodologie et résultats : Un suivi hebdomadaire de la dynamique de cette activité dans les 16 sites dortoirs des chauves-souris paillées a été réalisé d'a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
0
0
1
Order By: Relevance
“…This may be due to a probable reduction in food consumption, but also to possible dose/absorption interactions and a reduction in the amount of food absorbed [14]. Our results corroborate those of Niamien [15], who had already shown a decrease in animal weight under the influence of ethanolic extract of Ficus umbellata leaves. Analysis of variance of the blood counts of control and treated rats showed that blood platelet levels were significantly reduced compared with the control (p < 0.05) after 14 days for doses of 3000 and 5000 mg/Kg•BW.…”
Section: Discussionsupporting
confidence: 90%
“…This may be due to a probable reduction in food consumption, but also to possible dose/absorption interactions and a reduction in the amount of food absorbed [14]. Our results corroborate those of Niamien [15], who had already shown a decrease in animal weight under the influence of ethanolic extract of Ficus umbellata leaves. Analysis of variance of the blood counts of control and treated rats showed that blood platelet levels were significantly reduced compared with the control (p < 0.05) after 14 days for doses of 3000 and 5000 mg/Kg•BW.…”
Section: Discussionsupporting
confidence: 90%
“…Elle est située au centre de la ville d'Abidjan, elle-même localisée dans le sud de la Côte d'Ivoire (Figure 1). Dans sa partie centrale, les avenues sont ornées d'arbres d'espèces différentes, qui sont utilisés comme dortoirs par une importante population de chauves-souris paillées, espèce proche de la menace (Niamien et al, 2009 ;Niamien et al, 2010 ;Niamien et al, 2017 a ;Niamien et al, 2017b, Niamien et al, 2018a. L'intense animation de cette cité administrative les jours ouvrables, contraste fortement avec son calme des jours non ouvrables.…”
Section: Materiel Et Methodes Site D'étudeunclassified